Association Between Decreased Serum Albumin With Risk of Venous Thromboembolism and Mortality in Cancer Patients. (13th January 2016) - Königsbrügge, Oliver; Posch, Florian; Riedl, Julia; Reitter, Eva-Maria; Zielinski, Christoph; Pabinger, Ingrid; Ay, Cihan
Abstract: Background: In cancer patients, reduced serum albumin has been described as a marker for global declining health and poor prognosis. Our aim was to investigate the association of albumin concentrations with the occurrence of venous thromboembolism (VTE) and mortality in patients with cancer. Methods: This investigation was performed in the framework of the Vienna Cancer and Thrombosis Study (CATS), a prospective observational cohort study. We included 1, 070 patients with active cancer and assayed serum albumin from venous blood taken at study inclusion. Risk for occurrence of VTE was calculated in a proportional subdistribution hazard regression model with respect to competing risk of death and adjusted for cancer site, leukocyte count, estimated glomerular filtration rate, and cholinesterase. Results: Patients (630 males [58.9%] and 440 females [41.1%]) were observed for a median of 723 days. During follow-up, 90 VTE events (8.4%) and 396 deaths (37.0%) occurred. The median albumin was 41.3 g/L (25th–75th percentile, 37.6–44.2). Patients with albumin levels below the 75th percentile had a 2.2-fold increased risk of VTE (95% confidence interval [CI] 1.09–4.32), as well as a 2.3-fold increased risk of death (95% CI 1.68–3.20) compared with patients with albumin above the 75th percentile. Conclusion: Decreased serum albumin levels in cancer patients were significantly associated with increased risk of VTE and mortality. Serum albumin, a marker of a cancer patient's overall prognosis, could be considered for risk assessment of important clinical outcomes such as VTE and mortality. Abstract : In this study, serum albumin was measured in 1, 070 patients with active cancer. Decreased serum albumin levels were significantly associated with increased risk of venous thromboembolism and mortality.